Penerapan Teknologi Cloud Computing Untuk Aplikasi Repository Data Di Universitas Muhammadiyah Gorontalo - Wati, Nursetia; Lamusu, Rizal (Jurnal Teknologi Informasi Indonesia (JTII), 2019)
Current technological developments have supported all needs and requests for information for each individual through the creation of information presentation media, which is used to convey information as desired. In utilizing the technological development itself, researchers intend to apply Cloud Computing technology for data repositories at University of Muhammadiyah Gorontalo.Repository of this data is expected to help the performance of Academic and Supporting Staff and Students in the University of Muhammadiyah Gorontalo. The aim of this research is to be able to apply Cloud Computing technology for database repository applications so that it can help Lecturers and Academic Support Staff and Students for administrative and other purposes that can be stored in a database or file for later distribution using a computer network. This study conducted a stage that began by surveying whether the Muhammadiyah University of Gorontalo had applied this Cloud Computing technology to this data repository, then collected the data needed to create a Repository system. The output of this system was a Repository system containing data from Academic and Academic Support Staff and students at Muhammadiyah University, Gorontalo.